SCRATCH-BASED INTERACTIVE E-MODULES FOR PROMOTING JUNIOR HIGH SCHOOL STUDENTS’ COMPUTATIONAL THINKING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Qatrunnada, Azzura; Roemintoyo; Cahyono, Budi Tri (International Journal of Cultural and Social Science, 2026)
This study synthesizes recent evidence on Scratch-based interactive e-modules for supporting junior high school students’ computational thinking skills. Using a systematic literature review approach, 20 studies published between 2021 and 2026 were selected through a PRISMA-style screening process and analyzed descriptively and thematically. The findings indicate that Scratch-based learning is most effective when supported by scaffolding, project- or problem-based learning, integration with mathematics or science contexts, and explicit computational thinking assessment. Several Indonesian studies also report that Scratch-assisted e-modules are generally valid, practical, and potentially effective for supporting computational thinking development, although most studies remain limited to small-scale developmental research. This review suggests that interactive e-modules should be designed as contextualized, project-oriented, and scaffolded learning environments that encourage problem solving, reflection, and debugging practices in junior high school learning contexts.